Le Sang du Christ : sang eucharistique ou sang relique ? - Marc Venard (Tabularia)
There is an intriguing coincidence between the moment when the Latin Church abandoned the rite of receiving communion wine and the development of the cult of the "natural" precious Blood relic, of Christ on the cross. Might there be a link between the two phenomena? It is precisely in the twelfth century, when the devotion of the Precious Blood [relic] at Fécamp develops, that the latin Church terminates the practise of receiving communion wine. In the knowledge that the devotion of the Holy Blood widely expands in the twelfth century, the question arises whether this evolution more or less derived from the abandonment of the practise of receiving communion wine.